Needs Analysis for the Development of Content and Language Integrated Learning-Based Learning Modules in Civil Engineering Programs - Aflahatun, Nur; Januarius, Januarius; Fitriati, Sri Wuli; Pratama, Hendi (The Proceedings of English Language Teaching, Literature, and Translation (ELTLT), 2025)
Focusing on oral communication skills, this paper investigates the requirement of creating a CLIL-based English teaching module for Civil Engineering students at Universitas Pancasakti Tegal. Including English for Specific Purposes (ESP) into the curriculum becomes crucial as globalization expects engineering graduates to be competent in both technical expertise and English communication. By means of needs analysis, this study investigates important facets like learning objectives, language difficulties, curriculum integration, instructional module structure, and successful learning methodologies. Results show that although teachers deal with issues in resource availability and student involvement, students struggle with technical vocabulary, fluency, and structured oral communication. Still, chances present themselves through interactive learning techniques that improve students' competency including technical talks, project-based learning, and multimedia tools. To guarantee that students acquire the required oral communication skills for academic and professional success, the study suggests a CLIL-based teaching module combining engineering knowledge with communicative language exercises.